CHARACTER EDUCATION VALUES IN THE BOOK OF BIDAYATUL HIDAYAH WRITTEN BY IMAM AL-GHOZALI - Muhammad Fikri Abdun Nasir; Marini Binti Abd Rozak; Siti Fatonah (IAIN Padangsidimpuan, 2022)
The purpose of writing this article is to look at the character formation contained in the book Bidayatul Hidayah. This study is motivated by the Bidyatul Hidayah Book which is a book by Imam Al-Ghozali (ulama' in the VI H century) which is a very important book to be studied and used as a reference in character building. This research method is a literature review, namely by looking for books and articles about character education. The results showed that the values of character education in the book Bidayatul Hidayah are 1) Remembering Allah, 2) Discipline of Time, 3) Having good intentions, 4) Taking care of yourself, 5) Respect for parents, 6) Tolerance for educators and students, 7) Coconut milk to friends (friends) and ordinary people.